Comparison of the thermal behaviors and pollutant emissions of pelletized bamboo combustion in a fluidized bed combustor at different secondary gas injection modes. (1st December 2016) - Zhang, Li-hui; Chyang, Chien-Song; Duan, Feng; Li, Pin-Wei; Chen, Sing-Yu
Abstract: Staged combustion significantly affects the complete combustion of biomass and reduces pollutant emissions. This study primarily aimed to compare the thermal behaviors and pollutant emissions of different secondary gas injection modes in a pilot-scale fluidized bed combustor (FBC). Pelletized thorny bamboo was used as the fuel, and silica sand was used as the bed material. Flue gas recirculation (FGR) was employed. The experimental results demonstrate that the secondary gas injection modes in the FBC affected the combustion characteristics. The temperature of pelletized bamboo combustion with tangential injection mode (T mode) was lower than that of centripetal injection mode (C mode); however, T mode produced lower CO and NOx emissions than C mode because of the well-swirling effect. The secondary gas velocity and airflow distribution uniformity in the secondary gas layers jointly affect combustion, while T mode with four nozzles or C mode with two nozzles is optimal to reduce emissions. Furthermore, increasing the elevation of secondary air further reduces NOx emissions in C mode but does not significantly affect emissions in T mode. Highlights: Effect of secondary gas injection modes on the combustion behavior is studied. Bamboo combustion with T mode has lower temperature level, but smaller pollutant emissions. Secondary gas velocity and airflow distribution uniformity jointly affect combustion. T mode with four nozzles or C mode with two nozzles is optimal to reduce emissions. Increasing the elevation of secondary air further reduces NOx emissions in C mode.